2012
DOI: 10.1590/s1983-14472012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Classificação de pacientes internados em uma unidade traumatológica

Abstract: RESUMOEstudo com o objetivo de classificar pacientes de acordo com o grau de dependência da assistência de enfermagem, dimensionar a equipe de enfermagem e correlacionar os instrumentos utilizados. Foram utilizados os instrumentos de Perroca e Fugulin para classificar os pacientes internados durante 30 dias. O dimensionamento da equipe de enfermagem foi realizado conforme recomendação do Conselho Federal de Enfermagem. Incluiu-se 157 pacientes, sendo 42,0% classificados com o grau de dependência de cuidados in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
1
3
0
5
Order By: Relevance
“…The prevalence of semi-intensive 254 (46.5%) and intermediate 240 (44.0%) care categories is close to the results of other studies (11,(16)(17) that used patient classification instruments in clinical and surgical inpatient unitst with a predominance of elderly people, which led to greater complexity of care and demand for nursing care hours due to functional limitations and associated comorbidities.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The prevalence of semi-intensive 254 (46.5%) and intermediate 240 (44.0%) care categories is close to the results of other studies (11,(16)(17) that used patient classification instruments in clinical and surgical inpatient unitst with a predominance of elderly people, which led to greater complexity of care and demand for nursing care hours due to functional limitations and associated comorbidities.…”
Section: Discussionsupporting
confidence: 83%
“…This measurement scale for classification of the patient's degree of dependency is an instrument validated for the Brazilian scenario in medical and surgical adult inpatient units, which assesses aspects of nursing related to the standardization of care, proiding care, health education and emotional support (5,7) . Patient classification systems enable equalizing the relationship between the demand generated by patients and the care supply enabled by a number of nursing staff, in order to substantiate the adequacy of safer, quality care practices for patients and professionals, considering and adjusting situations of work overload (11) . In addition, these systems allow for the identification of changes in the healthcare complexity profile of hospitalized patients due to seasonality of diseases or an increase in chronic diseases resulting from the aging process and changes in the population profile (12) .…”
Section: Technological Advances Evidenced In Health Carementioning
confidence: 99%
“…In another study carried out in a hospitalization unit, the data were lower than those found in the sample, in which 50.3% required minimal care, 45.90% intermediate care, and 3.80% semi-intensive care. 19 It was observed among the three units analyzed that the hospitalization unit B presented 31.57% of intensive care and 14.5% of intermediate care, expressive value when compared to A and C. This high rate is due to the type of patient attended and the specificities presented. Unit B is part of a project linked to the Ministry of Health, being a reference in the institution to attend patients after a stroke.…”
Section: Discussionmentioning
confidence: 89%
“…Corroborando com os dados descritos, um estudo realizado com outra metodologia classificou pacientes quanto ao grau de dependência de enfermagem nos mesmos níveis, em unidades de internação médico-cirúrgicas em hospital universitário, identificando maior percentual de pacientes em cuidados intermediários, seguido de cuidados mínimos (15) . Outro estudo também apresentou uma maior demanda de pacientes que necessitam de cuidados intermediários (42%), seguido pelos cuidados mínimos (21,7%), alta dependência (32,5%) e cuidados semi-intensivos (3,8%) (16) .…”
Section: Discussionunclassified